Akhlak Berbuat Baik Terhadap Orangtua dalam Perspektif Al-Qur'an: Analisis QS. Al-Isra' 23-24 - Zaimuddin Zaimuddin; Ahmad Arifai; Muyasaroh Muyasaroh (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
This study discusses the morals of children towards their parents. This is focused on the good character of a child towards both parents in the perspective of the Qur'an (Surah Al-Isra ': 23-24). The choice of this topic is due to the large number of people who ignore His instructions and considering that in the current modernization era, the development of science and technology (science and technology) is so rapid, it is found that there are many cases of crimes from children against parents that occur because people forget about the importance of filial piety. to both parents. This study aims to answer the problem of what are the actions of ihsan and how to do good to parents and what is the perspective of the Qur'an on the morals of doing good to parents.This research is a library research using a qualitative approach that emphasizes the quality or most importantly the nature of a product/service. The most important thing about an item or service is an event/phenomenon/social phenomenon that contains the meaning behind the incident which can be used as a valuable lesson for the development of a theoretical concept. The related data in this study were collected through literature study, because this research is related to the understanding of the verses of the Qur'an. A study that uses reference sources in the form of the Qur'an, the interpretation of Quraish Shihab in his book "Tafsir Al-Misbah", moral books relevant to the discussion, libraries, and so on. The results of this study indicate that with all the weaknesses and limitations of humans in their senses and thoughts, humans cannot reach the truth as a whole, which makes many of those who do evil turn away from His guidance (Surah Al-Isra': 23-24 ), as well as the influence of the modernization factor which is marked by the rapid development of science and technology (science and technology) which has been wrongly used for its function, it is true that the negative impact of this can trigger people, especially children, to forget to respect their parents. So that this can be the cause of children who are rude and lose their sense of politeness and courtesy, even if it is towards their own parents.